Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T21:05:08+01:00
A) 3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
3x=1 /3
x=1/3

b) 4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
-x=1
x=-1

c) 4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
4x=8 /4
x=2

d) x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x=4

Pozdrawiam : ) ^^.
2010-03-21T21:06:08+01:00
A) 3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=8-9
-3x=(-1)/(-3)
x=1/3

b) 4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=6-5
(-1)x=1/(-1)
x=(-1)


c) 4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-3+15-4
4x=8/4
x=2

d)x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3+4-3
x=4